Export of organic carbon, nutrients and metals by the mid-sized Pechora River to the Arctic Ocean - Chupakov, Artem V.; Pokrovsky, Oleg S.; Moreva, Olga Y.; Kotova, Ekaterina I.; Vorobyeva, Taissia Y.; Shirokova, Liudmila S. (Chemical geology)
In contrast to good knowledge of export fluxes of carbon and metals from mainland to the Arctic Ocean by large Arctic Rivers, information on mid-sized rivers is limited, which prevents determining current status and foreseeing future changes in riverine export induced by climate change. Here we focused on one of the ‘middle eight’ Arctic rivers. The Pechora River (Swatershed = 322,000 km2) is the second largest European Arctic river draining through boreal forest and peatlands with partial (∼ 40%) permafrost coverage. Over 4 consecutive years (2015–2019), we measured weekly to monthly concentrations of carbon, major nutrients, and 40 major and trace elements in filtered (< 0.45 μm) river water at the terminal gauging stations for the Pechora River. The dependences between dissolved element concentration and river discharge over the full period of observation revealed 3 groups of major and trace solutes according to their seasonal behavior. Group 1 was comprised of Dissolved Inorganic Carbon (DIC), major anions (Cl, SO4), alkalis (Li, Na, K, Rb), alkaline-earth metals (Mg, Ca, Sr, Ba), elements present in the form of labile anions and neutral molecules (B, Si, Ge, Mo, Sb) and U. It demonstrated minimal concentrations during spring flooding and autumn high flow events, and maximal concentrations during winter base flow. Concentrations of these element negatively correlated with discharge. These elements primarily reflected the dominant sedimentary lithology of the Pechora catchment and were controlled by influx of underground waters hosted in carbonate rocks. Group 2 included DOC and low-mobility trivalent and tetravalent hydrolysates (Be, Al, Ga, Y, REEs, Ti, Zr, Hf, Th) and some trace metals (V, Cr, Cs, Nb). The transport of these elements to the river from the catchment likely occurred via surface and shallow subsurface waters due to leaching from organic-rich litter layer, and their concentrations positively correlated with discharge. Finally, group 3 involved major- (P, N, K) and micro-nutrients (Fe, Mn, Cu, Zn, Mo) and demonstrated features of both the 1st and 2nd groups as these elements originated from surface (organic-rich) and underground (sedimentary rock-hosted) sources and were removed by autochthonous biotic processes in the water column. As a result, the concentration of these nutrients exhibited a winter maximum and a summer minimum. Similar to other Arctic and subarctic rivers, the spring flood, which lasted from May to June, accounted for >50% of the annual export of DOC and generally insoluble trace metals. However, the winter baseflow provided sizable proportions of mobile elements such as DIC, major anions, cations, alkaline-earth elements, trace oxyanions and uranium. The size distribution of riverine solutes demonstrated 20–50% of DOC in the colloidal (3 kDa – 0.45 μm) form, dominance of low molecular forms (< 3 kDa) of soluble elements (alkali, alkaline earths, anions and neutral molecules) and essentially colloidal status of divalent metals (Cu, Zn, Cd, Pb, Ni), trivalent and tetravalent hydrolysates and U (from 30 to 93%). Seasonal variations in colloidal fractions of riverine solutes were consistent with the main mechanisms of element mobilization from the watershed to the Pechora River, as reflected in the 3 groups of elements according to their concentration – discharge relationship. Based on the present study and results of other mid-sized Arctic rivers (Severnaya Dvina, Taz), we demonstrate that mean discharges and solute concentrations in August can be used to adequately (± 20%) approximate mean annual values, hence allowing annual flux assessment via single month sampling campaign. A comparison of contemporary yields of Ca, Mg, Cl, SO4, DIC and DOC against historical data for the Pechora River basin demonstrated reasonable agreement within the inter-annual variations that is consistent with long-term data series on other Arctic rivers.